Karyotyping software with abnormalities detection - Pascual, Lester A. (Animo Repository, 2006)
A karyotype is an arrangement of chromosomes of a cell. It helps determine if there are abnormalities present through chromosome count or changes in the structure. The research would be concerned with human samples. Normal males and females have 46 chromosomes so an increase of decrease would help determine if there are abnormalities present in the sample. The research is about the creation of a karyotyping software that would help in determining if abnormalities are present in a given sample. A graphical user interface is generated to allow the user to select a sample from the computer and make a karyotype output. The significance of the research is to make karyotyping of medical practitioners easier and faster.